2023
DOI: 10.1007/s00345-023-04383-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging (MRI) for local staging before salvage radical prostatectomy: a meta-analysis

Abstract: Purpose The reliability of magnetic resonance imaging (MRI) as a local and nodal staging tool in radio-recurrent prostate cancer (PCa) is still unclear. The present study aims at evaluating the predictive value of MRI in the detection of extracapsular extension (ECE), seminal vesical invasion (SVI) and nodal involvement (LNI) in patients after primary radio (EBRT) and/or brachytherapy (BT) before salvage radical prostatectomy (SRP). Methods This systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A meta-analysis assessing the diagnostic performance of MRI in radiorecurrent prostate cancer reported that the sensitivities for extracapsular extension, seminal vesicle invasion, and lymph node involvement were 53%, 53%, and 33%, respectively. 12 Preoperative T-staging using MRI was similar or inferior in the present study. Regarding the discordance of the Gleason grade group in salvage RARP, the data from the Martini-Klinik Prostate Cancer Center showed downgrading, concordance, and upgrading of 19.6%, 45.1%, and 35.3%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…A meta-analysis assessing the diagnostic performance of MRI in radiorecurrent prostate cancer reported that the sensitivities for extracapsular extension, seminal vesicle invasion, and lymph node involvement were 53%, 53%, and 33%, respectively. 12 Preoperative T-staging using MRI was similar or inferior in the present study. Regarding the discordance of the Gleason grade group in salvage RARP, the data from the Martini-Klinik Prostate Cancer Center showed downgrading, concordance, and upgrading of 19.6%, 45.1%, and 35.3%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…Further, it can be challenging to detect recurrence in the field of brachytherapy implants. A recent meta-analysis of mpMRI of radiorecurrent PCa demonstrated that mpMRI has high specificity but limited sensitivity for local and nodal radiorecurrent PCa [35]. The use of novel positron emission tomography (PET) agents in combination with mpMRI has been shown to improve the sensitivity, specificity, and localization for primary PCa [36][37][38].…”
Section: Multiparametric Magnetic Resonance Imaging Of the Prostatementioning
confidence: 99%